Cross-layer Mobile Chord P2P protocol design for VANET. (1st September 2010) - Liu, Che-Liang; Wang, Chih-Yu; Wei, Hung-Yu
Efficient content distribution is one of the emerging applications in vehicular networks. To provide scalable content distribution in vehicular networks, Chord Peer-to-Peer (P2P) overlay could be applied. Most P2P protocols, including Chord, are designed for wired-line network, and might perform poorly in mobile networks. Mobile Chord (MChord) is proposed to enhance the P2P performance over Vehicular Ad hoc Network (VANET). In addition, cross-layer design to improve MChord performance in VANET is also investigated. Extensive NS-2 simulations with vehicular mobility traces are conducted to evaluate the P2P overlay performance in VANET. MChord and its cross-layer design outperforms the original Chord in various aspects, including application layer forwarding steps, query response ratio, correct query response ratio, and application delay.